Economic Fiqh Analysis on Cryptocurrency as a Payment Instrument in Islam - Siregar, Nurul Qosimah; Harahap, Nikma Sari; Fitri, Anisa Tul; Hulwati, Hulwati; Duhriah, Duhriah (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2025)
The use of cryptocurrencies as a payment instrument is an interesting social phenomenon to discuss. The use of cryptocurrencies as an official payment instrument is still prohibited by Bank Indonesia, but the use of cryptocurrencies continues to grow in Indonesia. BI limits the use of cryptocurrencies only as assets to be invested, not as legal tender. This research aims to analyze the law of cryptocurrency as a payment instrument from the perspective of economic fiqh. The data analysis technique in this study uses a qualitative analysis method that is descriptive-analytical. The researcher analyzed the suitability of the characteristics of cryptocurrency as a payment instrument with the principles of economic fiqh. A conceptual approach is used to explain the concept of cryptocurrency and a normative-theological approach is used to relate the concept to the provisions of Islamic law. The results of the study show that cryptocurrencies can, in principle, be recognized as objects of legal ownership (maal mutaqawwam) in Islam because they have value, can be owned and transferred. Cryptocurrencies can be used as a medium of exchange in Islam on a limited basis, if their use complies with Sharia principles: it is done transparently, free from speculation and usury, and supported by legitimate authorities and systems that guarantee clarity of value and security of transactions. This research emphasizes the importance of developing regulations that are adaptive to digital financial technology, as well as the need to emphasize transparency and avoidance of practices that are contrary to Islamic economic principles.Keywords: Cryptocurrency; Economic Fiqh; Payment Instrument.